The Role of Sirtuin-1 in Immune Response and Systemic Lupus Erythematosus - Qiu, Yueqi; Zhou, Xingyu; Liu, Yu; Tan, Siqi; Li, Yaping (Frontiers in Immunology, 2021)
Systemic lupus erythematosus (SLE) is a potentially fatal multisystem inflammatory chronic disorder, etiology and pathogenesis of which remain unclear. The loss of immune tolerance in SLE patients contributes to the production of autoantibodies which attack multiple organs and tissues, such as skin, joints, and kidneys. Immune cells play important roles in the occurrence and progression of SLE through the amplified immune responses. Sirtuin-1(SIRT1), a NAD+-dependent histone deacetylase, has been proved to be a pivotal regulator in various physiological processes, including cell differentiation, apoptosis, metabolism, aging and immune responses, via modulating different signaling pathways, such as nuclear factor κ-light-chain-enhancer of activated B cells (NF-κB) and activator protein 1 (AP-1)pathways. Recent studies have provided evidence that SIRT1 could be a regulatory element in immune system whose altered functions are likely relevant to SLE development. This review aims to illustrate the functions of SIRT1 performing in different types of immune cells, the potential roles of SIRT1 in the SLE pathogenesis and its therapeutic perspectives.